Antecedents of Electric Vehicle Adoption Intention in Indonesia: Insights into Willingness to Pay, Environmental Awareness, and Environmental Cognitions - Syelbi Huriyah Baradja; Rini Kuswati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The purpose of this study is to analyze the insights into willingness to pay and environmental factors of attitude-intention on electric vehicle adoption in Indonesia. This research used a quantitative research method in the form of a survey using a purposive sampling technique applied to 220 respondents who planned to use electric vehicles. We used Multivariate Data Analysis, as the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, to analyse the data through SmartPLS Version 4.0. The findings showed that: willingness to pay positively and significantly affects the intention to adopt electric cars; environmental awareness positively but insignificantly affects the intention to adopt electric cars. Environmental cognition negatively influences intention to adopt electric vehicles.In addition, willingness to pay has a significant positive effect on perceived value, while environmental awareness has a negative and insignificant effect, and environmental cognition produces the same results. This study shows that perceived value has a significant positive effect on the intention to adopt electric vehicles and mediates the relationship between willingness to pay and environmental cognition in the intention to adopt. Overall, the data confirms that willingness to pay and environmental awareness reinforced by "perceived value" are significant factors in increasing the intention of Indonesian people to use electric cars.